Using the principle of algorithm hybridization to maintain a high level of security in cloud storage - Rasha Muhseen Hadi; Barakat Saad Ibrahim; Seror Manea Bahloos (Genius Journals, 2023)
If the level of security is not in the process of protecting the stored data, then cloud computing security is one of the best options. Quite a few algorithms have been used in many researches for the purpose of cloud computing security. In this manuscript, a hybrid algorithm based on the working principle of an algorithm (ECC ) and an algorithm (AES ) was used in order to obtain a high amount of protection. In the first part of this manuscript, the study of the concepts of obfuscation and the safety of this technique was discussed, and then we conducted an evaluation process for this algorithm, where the results of hybridization of the algorithms used and when they work together provide additional features that ensure high performance and excellent data protection
Keywords: cloud computing; algorithm hybridization; data security